DECOLONISING LEGAL EDUCATION IN SOUTH AFRICA: A REVIEW OF AFRICAN INDIGENOUS LAW IN THE CURRICULUM (The Pretoria Student Law Review, 2021)
The student demonstrations in universities, which began in 2015, demanded the decolonisation of higher education. The demands included free education and a decolonised curriculum. In the field of law, the demand is anchored in changing the law curriculum. The central issues accompanying the demand are the status of indigenous law, legal history, concept of law, how law is taught and the role of law in African societies. The article examines the necessity of decolonising legal education in relation to the curriculum and the teaching of law in South African universities. The article adopts a doctrinal approach to assess the need to transform the curriculum. The article is grounded in the theory of Afrocentricity in a bid to revive the African paradigm and to examine legal epistemology in post-colonial South Africa. The argument developed in this article is that the legal education system has not significantly been decolonised since 1994. Arguably, the education system is founded on European theories and systems, hence difficult or impossible for the students in Africa to relate. This article recommends that a new curriculum that reflect laws, principles and customs of the African people must be introduced in the South African legal education. Institutions are also encouraged to take positive steps to decolonise legal education and end eurocentrism.1
Keywords: Living indigenous law; Decolonisation of legal education; Legal education